Strengthening Local Government Organisation Capacity for Adaptive Development Policy Responsive to Community Needs - Franky Djafar; Rifka S. Akibu; Puthisat Namdech (Journal of Contemporary Governance and Public Policy, 2025)
This study examines how to strengthen institutional capacity for regional development planning in Gorontalo Regency, Indonesia, with a focus on policies that are responsive to local community needs. A qualitative case study design was employed, drawing on in-depth interviews, observations, and analyses of planning documents, including the Regional Medium-Term Development Plan and the Regional Annual Work Plan. The findings indicate that robust institutional capacity, inclusive public participation, and the effective use of information technology are pivotal to producing adaptive and sustainable development policy. However, two principal challenges persist: insufficiently trained human resources for adaptive planning and the suboptimal use of information technology. The analysis links these results to the Sustainable Development Goals (SDGs)—notably SDG 11 (sustainable cities and communities) and SDG 16 (strong, transparent, and accountable institutions). Strengthening institutional capacity and deepening participation are expected to accelerate local SDG progress and to support the design of more inclusive, efficient, and data-driven policy. The study contributes to understanding—and improving—the implementation of adaptive, sustainable regional development policy amid social, economic, and environmental change.